PENGARUH KREATIVITAS GURU TERHADAP PRESTASI BELAJAR SISWA PELAJARAN IPS SMP SE-KECAMATAN SUKAJADI PEKANBARU - Putri Clawson; Siti Halimah Sa’diah (P3M STKIP 'Aisyiyah Riau, 2020)
This study aims to find out and analyze how much influence the creativity of teachers on student achievement in junior high schools in the City of Pekanbaru. The method used in this research is quantitative descriptive with a sample of 36 social science teachers in Sukajadi Subdistrict, Pekanbaru City. Data collection tools used are Questionnaire and Documentation. Based on the results of the research and discussion above conducted on 36 respondents in social studies teachers in Sukajadi Subdistrict, the results of the study found that there was a significant influence of teacher teaching creativity on students' learning achievements in Social Studies students in Sukajadi Subdistrict, with a value of R = 841, which means Teacher creativity contributed to the achievement of students 'social studies subjects by 70.7% or the achievements of students' social studies subjects was 70.7% influenced by the creativity of teachers in teaching, while the rest were influenced by other factors. The implications of this study are expected that social studies subject teachers can increase their creativity in teaching, by attending training or being active in KKG activities.